Pencapaian Standar Nasional Pelayanan Kesehatan Peduli Remaja pada Posyandu Remaja di Surabaya - Fitriani Putri Eka Ningsih (Universitas Airlangga, 2018)
Since 2010, Surabaya has a teen integrated service post (Posyandu) to solve teenagers' problem, but there were still a lot of teenagers' problem in Surabaya, such as early marriage. This study aims to determine about National Standard achievement of teen health care services at integrated service posts in Surabaya. This research used a cross-sectional design with a qualitative descriptive approach. The interview was conducted in 15 teen integrated service posts in Surabaya, and the respondents were the coordinator of teenage integrated service post. The results showed that the assessments of services and networking standard were difficult to achieve since teenagers' interest and socialization were not well organized. Also, there were no specific guidelines for teenagers, so the officers should guess and make their own guidelines. Lots of teen integrated service posts in Surabaya did not complete the form of evaluation and did not record and report their activities. The lack of health management in teen integrated service post influences the achievement of PKPR National Standard.   Keywords: health care service, integrated service, National standard, teenage.